A solar-driven photoelectrochemical platform based on Ag-sensitized TiO2 NTAs for pollutant treatment and hydrogen generation. Issue 19 (1st October 2021) - Hou, Junwei; Ning, Yanbin; Lu, Yuan; Zhi, Keke; Liu, Yansheng; Chen, Mengmeng; Wang, Qingyao
Abstract: Nanofunctional photocatalysts are attractive materials in solar energy transformation for environmental protection and green energy source generation. TiO2 nanoparticles are the most prospective photocatalysts due to the high photoactive property. In this paper, Ag nanoparticle-sensitized TiO2 nanotube arrays (Ag/TiO2 NTAs) were constructed as the photoelectrochemical platform for pollutant removal and hydrogen generation. TiO2 NTAs were firstly obtained by the anodization method, and carbon layer was formed by the hydrothermal carbonization of glucose in different concentrations, and then Ag nanoparticles were deposited by carbon reduction of Ag + . Ag/TiO2 NTAs could effectively decompose organic dye molecules and remove toxic heavy metal ions. The samples also could achieve visible light photocurrent and hydrogen generation. The surface plasmon resonance absorption and electron transfer path of Ag nanoparticles benefit photochemical performance improvement of TiO2 NTAs. The construction of multifunctional platform of Ag/TiO2 NTAs would cause extensive response and focus in the synergistic applications of semiconductor photocatalysts.